(untitled) (Research, Society and Development, 2020)
The monitoring of hydroclimatic variations associated with land use changes is essential in the analysis of risks and prevention of natural disasters. The objective of the study is to analyze the relationship between climatic indexes and precipitation, and is with the fluvial regime over a period of 34 years (1983-2016), observing the changes in land use (1988-2018) in the municipality of Cuiabá- MT. Climate index data from the National Oceanic and Administration Atmospheric were used; hydrological data from the National Water Agency; estimated rainfall data from the Global Precipitation Climatology Center and land use from the MapBiomas Project. The data was organized and the statistical adjustment indexes were calculated, in addition to using geoprocessing tools from the Geographic Information System to produce the land use map. In some extreme years, the influence of climate on local precipitation was observed. Hydrometeorological seasonality was characterized in the rainy seasons (Nov-Mar) and the dry season (Abr-Out); and the rain spatialization increasing in the west-east direction, with the validation of the data (measured x estimated) with excellent adjustment. Land use showed intense deforestation due to the advance of pasture areas. The river system showed decreasing trends, even with the increasing rainfall regime and the use of land favoring the increase in the flow of water discharge.